Impact of the VTE-PREDICT calculator on clinicians’ decision making in fictional patients with venous thromboembolism: a randomized controlled trial - Daniël Duijzer; Maria A. de Winter; Marc Carrier; Alexander T. Cohen; John-Bjarne Hansen; Karin A.H. Kaasjager; Ajay K. Kakkar; Saskia Middeldorp; Henrik T. Sørensen; Frank L.J. Visseren; Philip S. Wells; Jannick A.N. Dorresteijn; et al. (Research and Practice in Thrombosis and Haemostasis)
Background: After 3 months of anticoagulation for venous thromboembolism (VTE), the decision needs to be made whether to stop anticoagulation or extend treatment indefinitely. The VTE-PREDICT calculator can be used to estimate individual risks of VTE recurrence and bleeding to guide this decision. Objectives: To evaluate the impact of predicted individual risks of recurrence and bleeding on clinicians’ decisions on anticoagulation duration and to assess usefulness of the VTE-PREDICT calculator. Methods: A randomized controlled trial and within-subject study was conducted among clinicians treating VTE patients. The clinicians were asked to complete an online survey containing 6 fictional case vignettes. Group A proposed anticoagulant duration for each case without additional information first and subsequently after seeing calculator-predicted risks (within-subject analysis). Group B was directly provided with calculator risks and proposed treatment duration for each case vignette (for comparison with group A results in a randomized controlled trial analysis). Then, group B received questions on usefulness and credibility of the calculator. Results: Forty-five clinicians were assigned to group A and 48 to B. Overall, group A did not propose different anticoagulation durations than group B. However, individual clinicians in group A changed proposed duration in 35% of the cases after seeing the calculator risks. The calculator was considered useful and credible by most clinicians. Conclusion: Overall, use of the VTE-PREDICT calculator did not affect proposed anticoagulation duration. However, individual clinicians frequently changed their proposed duration after using the calculator, especially for patients with high bleeding risk.